2007
DOI: 10.1111/j.1745-4514.2007.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Freshness Loss in Sierra Fish (Scomberomorus Sierra) Muscle Stored in Ice as Affected by Postcapture Handling Practices

Abstract: Postmortem biochemical changes of sierra fish muscle kept in ice over a 15‐day storage period were investigated. The experimental sample (ES), fish sample handled under controlled postcapture conditions and the commercial sample (CS), handled by domestic fishermen, were thoroughly compared. The K value increased linearly for both samples; however, the slope for the CS sample was 1.5‐fold higher than that for the ES. K values after 15 days on ice were 82% and 43% for CS and ES, respectively. Trimethylamine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
4
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
2
13
4
2
Order By: Relevance
“…In this study, ATP and ADP content at Day 0 were 0.11 and 0.88 µmol/g muscle, respectively, which suggests that these compounds had been catabolized during the struggle associated with capture and/or during the elapsed time from capture to analyses (Castillo-Yáñez et al, 2007). ATP and ADP degradation pattern for shrimp were similar to that reported for several crustacean species.…”
Section: Nucleotide Catabolism and K-valuesupporting
confidence: 81%
“…In this study, ATP and ADP content at Day 0 were 0.11 and 0.88 µmol/g muscle, respectively, which suggests that these compounds had been catabolized during the struggle associated with capture and/or during the elapsed time from capture to analyses (Castillo-Yáñez et al, 2007). ATP and ADP degradation pattern for shrimp were similar to that reported for several crustacean species.…”
Section: Nucleotide Catabolism and K-valuesupporting
confidence: 81%
“…A noticeable decrease is observed on day 3 in T2 (90.32%) and T4 (89.87%), although the value increases later. The previous could be attributed to decreased muscle pH, associated to lactic acid accumulation (Castillo-Yañez et al, 2007). Mohan et al (2012) reported that sardines with 1 and 2% chitosan coatings showed greater WRC than the controls, with initial values of 18.31 and final values of 14.71 and 16.51%, respectively, whereas the final control value was 9.83%.…”
Section: Water Retention Capacitymentioning
confidence: 99%
“…The pH behavior, almost constant during the storage, could be associated to TVB, which did not show a significant increased during the experiment. It is known that the pH increased is well related to TVB increased (Castillo-Yañez et al, 2007).…”
Section: Physical Analyses Phmentioning
confidence: 99%
“…El camarón es propenso al deterioro debido a su alto contenido de aminoácidos libres y otras sustancias solubles que pueden servir como nutrientes fácilmente digerible para el crecimiento microbiano (Zeng et al, 2005). Estudios sobre la vida útil de los productos marinos se han enfocado en la cuantificación de microorganismos, trimetilamina, compuestos volátiles, nitrógeno y oxidación lipídica (Ocano et al, 2009;Castillo et al, 2007) pero poco se ha enfocado en estudios de microbiología predictiva. Para la preservación de camarones el método más utilizado ha sido la refrigeración, aunque a bajas temperaturas el producto puede sufrir reacciones autolíticas propias del crecimiento de bacterias deteriorantes como Pseudomonas sp y Shewanella putrefaciens, contribuyendo así a la disminución de la calidad y tiempo de vida útil del camarón (Bono y Badalucco, 2012).…”
Section: Introductionunclassified